Getting Useful Information From Cricket Data Set Using Data Analytics Techniques Odi Cricket Team Performance Analysis Using Data Mining Classification Techniques - et. al., Dr Udayabhanu N P G Raju, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Data analytics is an important part of data science. It deals with analysing a data set and generating useful information from it. It is the basis for applying machine learning algorithms, prediction techniques, etc. In this work, ODI Cricket data set of the year 2018 is considered. From this data, useful information such as teams playing most of the matches, teams winning or losing most of the matches, monthly frequency of the matches, groundwise distribution is visualised in the graphical format. Also, a user can enter the name of a particular team and check its performance based on total matches played, total matches lost, total matches won in terms of runs or wickets, etc. This analysis is useful in predicting the performance of a team in future matches. This can also be used to improve the results in future matches.